It’s all rubbish: Notes on OHS in the waste industry - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2024)
Note to readers: this paper has not been reviewed or revised since it was prepared in 2021 in preparation for a webinar for the New Zealand Institute of Safety Management. The objectives of this background note are to: (1) complement a continuing professional development webinar for NZISM members (2) provide a preliminary research agenda for Victoria University of Wellington students carrying out a research project in partial fulfilment of the requirements for the Master's of Health (Workplace Health and Safety), providing research-based documents and legal decisions. This work is incomplete and requires further investigation of the waste industry in New Zealand and overseas trends. With one exception, special wastes and hazardous substances have not been included.